Determining the insulin secretion potential for certain specific G-protein coupled receptors in MIN6 pancreatic beta cells - Gencoglu, Hasan; Şahin, Kazım; Jones, Peter M. (Tubitak Scientific & Technological Research Council Turkey, 2019)
Background/aim: The polypeptide hormone insulin is essential for the maintenance of whole-body fuel homeostasis, and defects in insulin secretion and/or action are associated with the development of type 1 and type 2 diabetes. The aim of this study was to assess the role of some G-protein coupled receptors (GPCRs), GPR54, GPR56, and GPR75, and cannabinoid receptors CB1R and CB2R, in the regulation of pancreatic beta-cell function. Materials and methods: Insulin secretion from mouse insulinoma beta-cell line (MIN6) monolayers was assessed via insulin radioimmunoassay (RIA). Reverse transcription-polymerase chain reaction (RT-PCR) was used to assess the expression of some specific GPCRs and the other receptors by MIN6 pancreatic beta-cells. Results: The agonists were not found to be toxic for the MIN6 pancreatic beta-cells within the range of the doses used in this study, whereas insulin secretion altered depending on the ligands and receptors. In addition, arachidonyl-2'-chloroethylamide (ACEA), carbachol, chemokine (C-C motif) ligand-5 (CCL5), and exendin as well as phorbol myristate acetate (PMA) ligands showed significant increases in the insulin secretion of MIN6 pancreatic beta-cells. Conclusion: Understanding the normal beta-cell function and identifying the defects in beta-cell function that lead to the development of diabetes will generate new therapeutic targets.
Keywords: Pancreatic B cells; G-protein coupled receptors; MIN6; diabetes mellitus; cell culture